The Effect of Customer Satisfaction and Customer Loyalty on Service Quality Through Customer Brand Image of Unej Medical Center (UMC Clinic) - Meviabriani Soraya; Isti Fadah; Mochammad Farid Afandi (International Forum of Researchers and Lecturers, 2026)
This study aims to analyze the effect of customer satisfaction and customer loyalty on service quality through brand image as a mediating variable among customers of UNEJ Medical Center (UMC Clinic). This research employs a quantitative approach with an explanatory design. The population consists of all UMC Clinic patients, with a sample of 115 respondents selected using purposive sampling technique. Data were collected through questionnaires and analyzed descriptively, supported by a literature review. The results show that customer satisfaction and customer loyalty have a positive effect on service quality, both directly and indirectly through brand image. Brand image acts as a mediator that strengthens the relationship between satisfaction and loyalty toward service quality. The practical implications of this study include the need to strengthen brand image, improve service quality across five main dimensions, and manage patient satisfaction and loyalty sustainably.